Analysis of Numeracy Literacy Skills in Terms of Self-Efficacy on Flat Shape Material for MTs Students - Ma'rifatullah, Fahris Ahmad; Madinina, Nur; Tsani, Dyan Falasifa; Cahyono, Budi (STKIP Singkawang, 2025)
Based on interviews with the mathematics teacher at MTs Negeri 1 Demak, it was found that students have difficulty translating word problems into mathematical form. This indicates that they have not yet achieved the first indicator of numeracy literacy. The teacher also observed that students’ self-efficacy affects their participation in learning, although it does not always align with their understanding of the material. This study aims to describe the numeracy literacy skills of eighth-grade students at MTs Negeri 1 Demak based on their level of self-efficacy, particularly on the topic of plane geometry. The research employed a descriptive qualitative method with six purposively selected subjects out of 32 students, representing high and moderate self-efficacy categories. Data were collected through numeracy literacy tests in the form of word problems, self-efficacy questionnaires, and in-depth interviews. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, with method triangulation to ensure data validity. The results show that students with high self-efficacy tend to have better numeracy literacy skills, especially in formulating situations into mathematical models, using appropriate procedures, and evaluating results in context. However, there were also students with high self-efficacy who had low numeracy literacy skills, indicating that confidence does not always correspond to mastery of concepts and procedures. Conversely, students with moderate self-efficacy but high numeracy skills performed well cognitively, although they still showed hesitation in answering questions. These findings highlight the importance of integrating self-efficacy development with conceptual reinforcement in mathematics learning. Stable self-efficacy can encourage students to be more confident, but it must be accompanied by adequate conceptual understanding and contextual practice to improve overall numeracy literacy quality.Analisis Kemampuan Literasi Numerasi Ditinjau dari Self-Efficacy Pada Materi Bangun Datar Siswa MTsABSTRAKBerdasarkan hasil wawancara dengan guru matematika MTs Negeri 1 Demak, ditemukan bahwa siswa mengalami kesulitan dalam mengubah soal cerita ke dalam bentuk matematika. Di mana hal tersebut menenjukkan bahwa siswa belum memenuhi indikator pertama dari literasi numerasi. Guru juga menemukan bahwa self-efficacy siswa memengaruhi partisipasi dalam pembelajaran, meski tidak selalu sejalan dengan pemahaman materi. Penelitian ini bertujuan untuk mendeskripsikan kemampuan literasi numerasi siswa kelas VIII MTs Negeri 1 Demak berdasarkan tingkat self-efficacy, khususnya pada materi bangun datar. Metode yang digunakan adalah deskriptif kualitatif dengan enam subjek penelitian yang dipilih secara purposive dari 32 siswa berdasarkan kategori self-efficacy tinggi dan sedang. Pengumpulan data dilakukan melalui tes literasi numerasi berbentuk soal cerita, angket self-efficacy, dan wawancara mendalam. Data dianalisis melalui tahap reduksi, penyajian, dan penarikan kesimpulan, dengan triangulasi metode untuk memastikan keabsahan data. Hasil penelitian menunjukkan bahwa siswa dengan self-efficacy tinggi cenderung memiliki kemampuan literasi numerasi yang lebih baik, terutama dalam merumuskan situasi ke dalam bentuk matematika, menggunakan prosedur yang tepat, serta mengevaluasi hasil secara kontekstual. Namun, terdapat pula siswa dengan self-efficacy tinggi yang memiliki kemampuan literasi numerasi rendah, yang menunjukkan bahwa keyakinan diri tidak selalu sejalan dengan penguasaan konsep dan prosedur. Sebaliknya, siswa dengan self-efficacy sedang tetapi kemampuan numerasi tinggi menunjukkan performa baik secara kognitif namun masih diliputi keraguan dalam menjawab soal. Temuan ini menekankan pentingnya integrasi antara pembinaan self-efficacy dan penguatan konsep dalam proses pembelajaran matematika. Self-efficacy yang stabil dapat mendorong siswa lebih percaya diri, tetapi harus dibarengi dengan pemahaman konseptual dan latihan kontekstual yang memadai untuk meningkatkan kualitas literasi numerasi secara menyeluruh.Kata Kunci :Literasi numerasi; self-efficacy; bangun datar